2016
DOI: 10.9790/0853-151002113116
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Spectrum of Non-Malignant Lesions of Gastrointestinal Tract- An Institutional Study.

Abstract: Abstract:Background: Gastrointestinal tract (GIT)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
(7 reference statements)
2
2
0
Order By: Relevance
“…A study done by Sabharwal., et al [18] and Kamal.,et al [11] support this trend, which is specified by their figures. Gastrointestinal (GI) cancers account for about 20% of estimated new cancer cases and 15% of estimated mortality worldwide [1]. Organ-wise distribution of malignancies in our study signifies the most common organ involved were co-lon, rectum and anal canal (43.7%) with least common being tumors involving the small intestine (2.2%), which is in accordance with other studies in literature carried out by Kamal., et al [11].…”
Section: Colo-rectumsupporting
confidence: 91%
See 1 more Smart Citation
“…A study done by Sabharwal., et al [18] and Kamal.,et al [11] support this trend, which is specified by their figures. Gastrointestinal (GI) cancers account for about 20% of estimated new cancer cases and 15% of estimated mortality worldwide [1]. Organ-wise distribution of malignancies in our study signifies the most common organ involved were co-lon, rectum and anal canal (43.7%) with least common being tumors involving the small intestine (2.2%), which is in accordance with other studies in literature carried out by Kamal., et al [11].…”
Section: Colo-rectumsupporting
confidence: 91%
“…Given its sheer length and extent, there is a possibility of various pathologies affecting individual segments of the entire tract. Ranging from congenital anomalies, inflammatory conditions to neoplastic conditions including both, benign as well as malignant lesions, the spectrum of diseases which can occur individually or in combination with various segments is wide [1].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study 50(9.76%) specimens were from esophagus, of which 43 (86%) were neoplastic with 42 (97.6%) were malignant tumors and one (2.4%) case was of leiomyoma .Among the malignant lesions all were squamous cell carcinomas. The affected age group in our study various form 21-80 years with more commonly affected age group beign 51-60 years which was similar to studies reported by Sunitha Bamanikar et al 1 and Khatib et al 11…”
Section: Esophagussupporting
confidence: 91%
“…However, yet another study by Khatib W M et al [26] showed a slightly altered report in which the non-neoplastic lesions observed in 75.29% of cases and the neoplastic lesions were seen in 24.71% of cases. The variation in the results may due to personal, nutritional and environmental factors of the individuals.…”
Section: Total 113 100mentioning
confidence: 93%